Continued Beneficial Effects of Burosumab in Adults with X-Linked Hypophosphatemia: Results from a 24-Week Treatment Continuation Period After a 24-Week Double-Blind Placebo-Controlled Period - Portale, A; Carpenter, T; Brandi, M; Briot, K; Cheong, H; Cohen-Solal, M; Crowley, R; Jan De Beur, S; Eastell, R; Imanishi, Y; Imel, E; Ing, S; et al. (Springer Nature, 2019)
Burosumab, a fully human monoclonal antibody to FGF23, is the only approved treatment for X-linked hypophosphatemia (XLH), a rare genetic disorder characterized by renal phosphate wasting and substantial cumulative musculoskeletal morbidity. During an initial 24-week randomized, controlled trial, 134 adults with XLH received burosumab 1 mg/kg (n = 68) or placebo (n = 66) every 4 weeks. After 24 weeks, all subjects received open-label burosumab until week 48. This report describes the efficacy and safety of burosumab during the open-label treatment period. From weeks 24-48, serum phosphorus concentrations remained normal in 83.8% of participants who received burosumab throughout and were normalized in 89.4% who received burosumab after placebo. By week 48, 63.1% of baseline fractures/pseudofractures healed fully with burosumab, compared with 35.2% with burosumab after placebo. In both groups, burosumab was associated with clinically significant and sustained improvement from baseline to week 48 in scores for patient-reported outcomes of stiffness, pain, physical function, and total distance walked in 6 min. Rates of adverse events were similar for burosumab and placebo. There were no fatal adverse events or treatment-related serious adverse events. Nephrocalcinosis scores did not change from baseline by more than one grade at either week 24 or 48. These data demonstrate that in participants with XLH, continued treatment with burosumab is well tolerated and leads to sustained correction of serum phosphorus levels, continued healing of fractures and pseudofractures, and sustained improvement in key musculoskeletal impairments.